Method for producing ti al alloy with precisely controlled content of spherulitic structure
Patent Information
- Application Number
- CN202611075992.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-20
- Publication Date
- 2026-10-09
AI Technical Summary
[0004]第一,该现有技术主要依赖常压条件下的固溶时效热处理诱发胞状反应,热暴露温度较高、工艺热负荷较大,容易引起片层组织粗化、晶粒长大以及类珠光体团簇粗化等问题,不利于获得尺度细小、分布受控的类珠光体组织
[0031]关于合金成分,本发明的发明人未采用Nb作为主要β稳定元素,而是选择Mn作为主要合金化元素之一,主要是考虑到Nb虽然能够稳定β/B2相并提高TiAl合金高温性能,但其密度较高、成本较高,且在TiAl合金中扩散相对较慢。相比之下,Mn同样具有稳定β/B2相和改善TiAl合金热加工性的作用,同时密度和成本相对较低,在较低温度下更有利于调控B2相、/α2片层界面及胞状反应界面的迁移行为。本公开通过Mn与少量Mo、W、B、C的协同合金化,在不依赖Nb含量调控的情况下,实现了TiAl合金在高温高压条件下发生受控类珠光体转变。
Smart Images

Figure CN122879629A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of TiAl alloy preparation, and more specifically, to a method for preparing a TiAl alloy in which the content of a pearlite-like microstructure is precisely controlled. Background Technology
[0002] TiAl alloys are an important new type of high-temperature lightweight structural material, characterized by low density, high specific strength, good creep resistance, and high-temperature oxidation resistance, showing significant application potential in aerospace, automotive engines, and high-temperature structural components. However, TiAl alloys have low room-temperature plasticity and fracture toughness, a narrow hot working window, and their microstructure, especially... The proportion, morphology, and spatial distribution of the α2 lamellar structure, B2 phase, and pearlite-like structure have a significant impact on the overall mechanical properties of the alloy. Therefore, controlling the microstructure of TiAl alloys through heat treatment or other external fields is an important technical approach to improve their overall performance.
[0003] To address this, there are methods for controlling the microstructure of TNM-type TiAl alloys. Firstly, forged or hot-rolled equiaxed near-... TNM alloy samples were solution-treated, held at temperature, and then air-cooled to form an extremely fine nanosheet structure. Subsequently, aging treatment was performed, held at temperature, and then furnace-cooled, triggering a cellular reaction that transformed some of the nanosheet structure into a pearlitic structure, forming a pearlitic microstructure. This method can improve the high-temperature strength and ductility of TNM alloys at 750℃ to some extent, but it has some drawbacks, such as:
[0004] First, the existing technology mainly relies on solution aging heat treatment under normal pressure to induce cellular reactions. The heat exposure temperature is high and the process heat load is large, which can easily cause problems such as coarsening of lamellar structure, grain growth and coarsening of pearlite clusters, which is not conducive to obtaining pearlite structure with small scale and controlled distribution.
[0005] Second, the driving force for the microstructure transformation in this existing technology mainly originates from the phase transformation and diffusion processes during conventional heat treatment, without addressing the regulatory effect of high-pressure external fields on the phase stability, atomic diffusion behavior, interface migration behavior, and thermodynamic driving force of cellular reactions in TiAl alloys. Therefore, this method cannot solve the problem of inducing controlled cellular reactions in TiAl alloys at lower temperatures, nor does it disclose a technical solution for preparing pearlite-like microstructures under high temperature and high pressure conditions.
[0006] Third, this existing technology is applicable to TNM alloy systems with Nb, Mo, and B alloys, and is suitable for forged or hot-rolled equiaxed near-... The microstructure is the initial microstructure. This scheme does not specifically address the design of Ti-Al-Mn-Mo-WBC TiAl alloys, nor does it disclose a method for inducing pearlite-like microstructure formation through high-temperature and high-pressure treatment under conditions of synergistic alloying of Mn with small amounts of Mo, W, B, and C. Due to the high density and cost of Nb, and its relatively slow diffusion in TiAl alloys, the aforementioned TNM alloy system and its atmospheric pressure solution aging process cannot directly solve the problem of controlled preparation of pearlite-like microstructure in low-Nb or Nb-free Mn-Mo-WBC TiAl alloys.
[0007] Fourth, while the pearlite-like structure content in this prior art can reach no more than 50%, it may exhibit coarse and randomly distributed characteristics. For TiAl alloys, an excessively high pearlite-like structure content may weaken... The α2 lamellar tissue's primary load-bearing framework makes it difficult to achieve a balance between local deformation coordination and overall load-bearing capacity. Therefore, current technology still lacks a method to obtain a suitable amount of fine, controlled-distribution pearlite-like tissue at lower temperatures by externally controlling the cellular reaction driving force, while simultaneously preserving... Preparation method of α2 layered support skeleton.
[0008] In summary, while existing atmospheric pressure solution aging techniques can induce pearlite-like microstructures in TiAl alloys, they still suffer from drawbacks such as high processing temperatures, strong heat exposure, a high risk of microstructure coarsening, limited applicability to specific alloy systems, and a lack of high-pressure external field control mechanisms. They have not yet achieved controlled pearlite transformation in TiAl alloys at lower temperatures by controlling phase stability, interfacial migration behavior, and cellular reaction driving forces under high pressure, thus failing to achieve a pearlite-like microstructure that is compatible with... / α2 layered support skeleton organization and coordination.
[0009] Therefore, directional control of the microstructure of TiAl alloys has become a core technical approach to overcome their performance bottlenecks and improve their room temperature plasticity and fracture toughness. Summary of the Invention
[0010] In view of this, the inventors of this invention focus on inducing cellular reactions through solution aging treatment, driving the transformation of the original lamellar microstructure of TiAl alloys into a fine-grained pearlite-like microstructure, thereby synergistically improving the room-temperature plasticity and comprehensive mechanical properties of TiAl alloys. In particular, given that existing research mainly focuses on atmospheric pressure heat treatment conditions, and the exploration of microstructure evolution control mechanisms and corresponding process development under extreme load conditions remains lacking, the inventors have creatively proposed a method to precisely improve the comprehensive mechanical properties of TiAl alloys by accurately controlling the pearlite microstructure within them.
[0011] The core principle of this invention is to utilize high pressure to regulate the phase stability and atomic diffusion rate of TiAl alloy, thereby enhancing the thermodynamic driving force of cellular transformation. Cellular reactions can be induced at low temperatures without the need for a high-temperature solid solution step in the α single-phase region, achieving a partial transformation of the lamellar structure of TiAl alloy into a pearlite-like structure, and effectively avoiding the risk of microstructure coarsening caused by high-temperature aging treatment.
[0012] According to one aspect of the present invention, a method for preparing a TiAl alloy with precisely controlled pearlite content is provided, wherein the composition of the TiAl alloy, in atomic percentage terms, is Ti-(42-45)Al-(2-5)Mn-(0.1-0.5)Mo-0.4W-0.2(B,C), particularly preferably Ti-44Al-3Mn-0.4Mo-0.4W-0.2(B,C), and the volume fraction of pearlite-like structure is controlled at 8%-30%, specifically comprising the following steps:
[0013] Step 1: Ingredients
[0014] Weigh the raw materials according to the atomic percentage of each element in the alloy, mix them evenly. Specifically, convert the atomic percentage of each element in the alloy into the mass percentage of each raw material, weigh the corresponding mass of sponge titanium, high-purity aluminum, high-purity manganese, aluminum-molybdenum master alloy, aluminum-tungsten master alloy, titanium diboride, and titanium carbide as raw materials, and mix them evenly.
[0015] Step 2: Melting
[0016] The homogeneous raw materials obtained in step one are prepared into homogeneous ingots by means of, but not limited to, vacuum induction melting.
[0017] Step 3: Two-step heat treatment
[0018] The ingot with uniform composition obtained in step two is subjected to a two-step heat treatment to obtain the initial microstructure.
[0019] Specifically, it is called a two-step heat treatment because the alloy ingot obtained after melting undergoes two heat treatments. According to one embodiment of the present invention, preferably, in step three, the two-step heat treatment process includes first heating the ingot to 1200-1300°C, holding it at that temperature for 20-100 minutes, and then air-cooling it to room temperature; then heating the ingot to 850°C, holding it at that temperature for 2-5 hours, and then furnace-cooling it. More preferably, according to one embodiment of the present invention, in step three, the two-step heat treatment process includes first heating the ingot to 1270°C, holding it at that temperature for 30 minutes, then air-cooling it to room temperature; then heating the ingot to 850°C, holding it at that temperature for 3 hours, and then furnace-cooling it.
[0020] Step 4: Machining
[0021] The heat-treated ingot obtained in step three is machined into a cylinder with a certain length-to-diameter ratio by turning.
[0022] Step 5: High Temperature and High Pressure Experiment
[0023] The cylindrical ingot, machined in step four, is placed in a large-cavity high-temperature and high-pressure device and loaded for 3 to 5 hours under a pressure of 5 to 15 GPa and a temperature of 700 to 1000°C to obtain a pearlescent structure with the target content. The large-cavity high-temperature and high-pressure device is, for example, but not limited to, any one of the following: a German 1000-ton 6-8 mold large-cavity press, a Kawai type multi-face top press, a DIA type multi-face top press, a Walker type multi-face top press, or a domestic six-face top press.
[0024] According to one embodiment of the present invention, preferably, in step five, the pressure is 10 GPa.
[0025] According to one embodiment of the present invention, preferably, in step five, the temperature is 800°C and the loading time is 3 hours.
[0026] According to one embodiment of the present invention, preferably, in step five, the pressure is first increased to 10 GPa by gradually increasing the pressure, and then heated to 800°C at a heating rate of 100°C / min and held for 3 hours.
[0027] According to an embodiment of the present invention, preferably, in step five, after the target content of pearlescent tissue is obtained by enduring the pressure and temperature conditions for the specified loading time in the large cavity high temperature and high pressure device, it is rapidly cooled to room temperature, and finally restored to normal pressure by step-by-step depressurization.
[0028] This invention particularly favors a high-pressure treatment process of 800℃ for 3 hours. The purpose is not to repeat conventional atmospheric pressure aging, but to utilize high pressure to regulate the stability of each phase, interface migration behavior, and cellular reaction driving force in the TiAl alloy, enabling the formation of pearlite-like structures at temperatures significantly lower than traditional atmospheric pressure aging. Compared to solution treatment at 1250-1300℃ combined with atmospheric pressure aging at 930-980℃, the 800℃×3h high-temperature, high-pressure treatment of this invention effectively reduces the heat exposure temperature, mitigating lamellar coarsening, grain growth, and pearlite cluster coarsening caused by prolonged high-temperature holding. Simultaneously, long-range atomic diffusion is suppressed at lower temperatures, which is beneficial for obtaining finer-scale, more controlled-distribution pearlite-like structures, avoiding the formation of excessively coarsened or large-area interconnected pearlite-like regions.
[0029] According to an embodiment of the present invention, preferably, the obtained TiAl alloy partially transforms the microstructure with respect to the pearlite-like microstructure, wherein the TiAl alloy retains The α2 lamellar structure serves as the main supporting framework, and the content of the obtained pearlite-like structure in the TiAl alloy is 10% to 30%, more preferably 10% to 20%. According to an embodiment of the present invention, and even more preferably, the content of the pearlite-like structure is 10% to 18%.
[0030] That is, in this invention, after obtaining an initial microstructure dominated by uniform lamellar structure through batching, vacuum induction melting, and two-step preheating treatment, the ingot sample is placed in a large-cavity high-temperature and high-pressure device to obtain a TiAl alloy with a pearlite-like microstructure content of more than 10%. The inventors of this invention do not simply pursue a high pearlite-like microstructure content, but rather aim to coordinate and... A balance is achieved between the α2 lamellar structure and the load-bearing capacity. After comprehensive consideration, the volume fraction of the pearloid structure is preferably controlled at 8%-30%, and more preferably 10%-18%, in order to avoid excessive formation of the pearloid structure, which would weaken the lamellar load-bearing skeleton.
[0031] Regarding the alloy composition, the inventors of this invention did not use Nb as the main β-stabilizing element, but instead chose Mn as one of the main alloying elements. This was primarily because, while Nb can stabilize the β / B2 phase and improve the high-temperature performance of TiAl alloys, its high density and cost, coupled with its relatively slow diffusion in TiAl alloys, make it less susceptible to degradation. In contrast, Mn also stabilizes the β / B2 phase and improves the hot workability of TiAl alloys, while having a relatively lower density and cost, and is more conducive to controlling the B2 phase at lower temperatures. The migration behavior of the α2 lamellar interface and cellular reaction interface. This disclosure achieves a controlled pearlite-like transformation of TiAl alloys under high temperature and high pressure conditions through the synergistic alloying of Mn with small amounts of Mo, W, B, and C, without depending on the Nb content. Attached Figure Description
[0032] The above and other objects, features, and advantages of this disclosure will become more apparent through a more detailed analysis of the embodiments of this disclosure in conjunction with the accompanying drawings. The accompanying drawings are provided to further illustrate the embodiments of this disclosure and form part of the specification, serving to explain the disclosure together with the embodiments. They do not constitute a limitation of this disclosure, wherein:
[0033] Figure 1 A schematic diagram of the large-cavity high-temperature and high-pressure experimental apparatus and process flow used to prepare pearlite-like tissue according to Embodiment 1 of this disclosure is shown, wherein, Figure 1(a) is a schematic diagram of the loading device of the large cavity press, showing the compression state of the sample assembly under multi-directional pressure; Figure 1 (b) is a schematic diagram of the sample assembly structure used in high-temperature and high-pressure experiments; Figure 1 (c) shows the pressure and temperature change curves over time during the high temperature and high pressure experiment. The sample is first pressurized to 10 GPa, then heated to 800℃ and held for 3 hours, and then cooled and depressurized to normal pressure.
[0034] Figure 2 (a) and (b) show the microstructure of the alloy according to Example 1 of this disclosure at different magnifications before high-temperature and high-pressure testing, where the white contrast represents the B2 phase, and the alternating gray and black contrasts represent the microstructure. / α2 lamellar tissue.
[0035] Figure 3 Images (a), (b), and (c) show the microstructure of the alloy according to Example 1 of this disclosure at different magnifications after high-temperature and high-pressure testing, where the white contrast represents the B2 phase, and the alternating gray and black contrasts represent the microstructure. / α2 lamellar structure, with fine lamellar radial eutectoid structures formed at the boundaries and inside the lamellar structure, and the structure accompanied by alternating gray and white contrasts is a pearlitic structure.
[0036] Figure 4 (a) and (b) show the microstructure of the alloy according to Comparative Example 1 of this disclosure at different magnifications after heat treatment, wherein the white contrast represents the B2 phase, and the alternating gray and black contrasts represent the microstructure. / α2 lamellar tissue. Detailed Implementation
[0037] Exemplary embodiments of the present application will now be described in more detail with reference to the accompanying drawings. It should be understood that this disclosure should not be construed as limiting to the exemplary embodiments described herein, but rather that it can be implemented in various other forms; these exemplary embodiments are provided only for a more thorough and complete understanding of the present application. It should also be understood that the accompanying drawings are given by way of example only and are not intended to limit the precise form of the embodiments or to limit the scope of protection of the present application.
[0038] Example 1
[0039] This embodiment uses a Ti-44Al-3Mn-0.4Mo-0.4W-0.2(B,C) alloy as the object, and performs high-temperature and high-pressure treatment using a large-cavity press to obtain a controlled pearlitic microstructure. This process eliminates the need for the high-temperature solution treatment followed by medium-temperature aging required for traditional pearlitic microstructure preparation. Instead, it induces a cellular reaction under high-temperature and high-pressure conditions of 800℃ for 3 hours, achieving a partial transformation of the TiAl alloy's lamellar microstructure into a pearlitic microstructure.
[0040] The steps for obtaining pearloid-like tissue through high-temperature and high-pressure experiments are as follows:
[0041] Step (1) Ingredient preparation
[0042] The raw materials required for smelting and casting ingots are sponge titanium, high-purity aluminum particles, high-purity manganese particles, high-purity aluminum-molybdenum master alloy particles, high-purity aluminum-tungsten master alloy particles, high-purity titanium diboride powder, and high-purity titanium carbide powder. These raw materials are mixed uniformly according to the alloy composition ratio to prepare raw materials for vacuum induction melting.
[0043] Step (2) Smelting
[0044] The raw materials that are mixed evenly in step (1) are prepared into ingots by vacuum induction melting. The composition of the ingots is ensured by repeated remelting three times, and the vacuum degree of melting is less than 0.1 Pa.
[0045] Step (3) Two-step heat treatment and wire cutting
[0046] A homogeneous ingot was subjected to a two-step heat treatment process to obtain the initial microstructure. The two-step heat treatment process includes two steps: first, the ingot is heated to 1270℃, held for 30 minutes, and then air-cooled to room temperature; then, the ingot is heated to 850℃, held for 3 hours, and then furnace-cooled, thus obtaining the heat-treated alloy ingot. Subsequently, a sample was cut from the center of the ingot using a CNC wire cutting machine for initial microstructure observation. The sample was block-shaped, with a size of 6 mm. 6 6mm.
[0047] Step (4) Machining
[0048] The sample obtained in step 3 is machined, specifically turned, for use in the high-temperature and high-pressure treatment experiment in step (5) below. The sample is a cylinder with a size of φ3. 3mm.
[0049] Step (5) High temperature and high pressure treatment
[0050] The sample was placed in a Kawai-type multi-face press and kept at 10 GPa / 800℃ for 3 hours. It should be noted that the large-cavity press can be any of the following: a German 1000-ton 6-8 mold large-cavity press, a Kawai-type multi-face press, a DIA-type multi-face press, a Walker-type multi-face press, or a domestically produced six-face press.
[0051] Step (6) Microscopic tissue observation
[0052] The initial sample and the sample after high temperature and high pressure were mechanically polished until the surface was mirror-like and free of scratches. The initial tissue and the tissue after high temperature and high pressure were observed using a scanning electron microscope.
[0053] The schematic diagram of the working process of the large-cavity press in Example 1 is as follows: Figure 1 As shown, the pressure is first increased to 10 GPa through a stepwise pressurization process, then heated to 800℃ at a heating rate of 100℃ / min and held for 3 hours, followed by rapid cooling to room temperature, and finally depressurized stepwise to return to atmospheric pressure. Specifically, Figure 1 (a) is a schematic diagram of the loading device of the large cavity press, showing the compression state of the sample assembly under multi-directional pressure; Figure 1 (b) is a schematic diagram of the sample assembly structure used in high-temperature and high-pressure experiments; Figure 1 (c) shows the pressure and temperature change curves over time during the high temperature and high pressure experiment. The sample is first pressurized to 10 GPa, then heated to 800℃ and held for 3 hours, and then cooled and depressurized to normal pressure.
[0054] The microstructure of the TiAl alloy in Example 1 before and after the high temperature and high pressure experiment is as follows: Figure 2 and Figure 3 shown. Specifically, Figure 2 (a) and (b) show the microstructure of the alloy according to Example 1 of this disclosure at different magnifications before high-temperature and high-pressure testing, where the white contrast represents the B2 phase, and the alternating gray and black contrasts represent the microstructure. / α2 lamellar tissue; Figure 3 Images (a), (b), and (c) show the microstructure of the alloy according to Example 1 of this disclosure at different magnifications after high-temperature and high-pressure testing, where the white contrast represents the B2 phase, and the alternating gray and black contrasts represent the microstructure. / α2 lamellar structure, with fine lamellar radial eutectoid structures formed at the boundaries and inside the lamellar structure, and the structure accompanied by alternating gray and white contrasts is a pearlitic structure.
[0055] comprehensive Figure 2 and Figure 3It can be seen that the initial structure is mainly composed of alternating shades of gray and black. The microstructure consists of α2 lamellar tissue, with a small amount of white-contrast B2 phase distributed around the lamellar clusters. The microstructure after high temperature and pressure, in addition to... In addition to the α2 lamellar structure and the B2 phase, a large number of pearlite-like structures with alternating gray and white contrasts were formed at the boundaries and inside the lamellar structure. As shown in Table 1, the pearlite content obtained after the high temperature and high pressure experiment was approximately 15.2%.
[0056] Example 2
[0057] Except for the processing method in step (5), all other steps were performed in the same way as in Example 1. In other words, the sample obtained in step (4) of Example 1 was subjected to the high temperature and high pressure treatment in step (5) and the microstructure observation in step (6) of this Example 2. Therefore, it will not be described again. The specific parameters and results of step (5) are shown in Table 1 below.
[0058] Example 3
[0059] Except for the processing method in step (5), all other steps were performed in the same way as in Example 1. In other words, the sample obtained in step (4) of Example 1 was subjected to the high temperature and high pressure treatment in step (5) and the microstructure observation in step (6) of Example 3. Therefore, it will not be described again. The specific parameters and results of step (5) are shown in Table 1 below.
[0060] Example 4
[0061] Except for the processing method in step (5), all other steps were performed in the same way as in Example 1. In other words, the sample obtained in step (4) of Example 1 was subjected to the high temperature and high pressure treatment in step (5) and the microstructure observation in step (6) of Example 4. Therefore, it will not be described again. The specific parameters and results are shown in Table 1 below.
[0062] Comparative Example 1
[0063] This comparative example is a comparison example of obtaining a pearlitic structure under high temperature and high pressure in Example 1 above. It aims to demonstrate that holding at 800℃ for 3 hours verifies that high pressure promotes the formation of a pearlitic structure. Therefore, similar to Examples 2-4 above, the operation steps using the alloy ingots obtained in steps 1-4 of Example 1 are as follows:
[0064] Step (1) Heat treatment
[0065] The block sample was placed in a crucible, put into a heat treatment furnace, heated to 800℃ and held for 3 hours, and then rapidly cooled by water quenching.
[0066] Step (2) Microscopic tissue observation
[0067] The heat-treated sample was mechanically polished until the surface was mirror-like and free of scratches, and the microstructure was observed using a scanning electron microscope.
[0068] The microstructure of the TiAl alloy in Comparative Example 1 after holding at 800℃ for 3 hours is as follows: Figure 4 shown. Specifically, Figure 4 (a) and (b) show the microstructure of the alloy according to Comparative Example 1 of this disclosure at different magnifications after heat treatment, wherein the white contrast represents the B2 phase, and the alternating gray and black contrasts represent the microstructure. / α2 lamellar structure. It can be seen that the microstructure consists of alternating gray and black contrasts. The structure consists of α2 lamellar tissue and a white-contrast B2 phase. Compared to... Figure 2 The initial microstructure showed that after incubation at 800℃ for 3 hours, only the content of the B2 phase increased slightly, and no pearlite-like formation was observed.
[0069] Table 1: Content of various microstructures in the alloy under different processing techniques. (Note: The content was quantitatively measured by Image J image analysis software. To ensure statistical accuracy, four BSE-SEM images were randomly selected for each process group for measurement. The final result was the average value. The so-called initial microstructure refers to the microstructure obtained by steps (1) to (4) in Example 1 before high temperature and high pressure treatment.)
[0070] Table 1: Experimental conditions and corresponding results for each embodiment and comparative example
[0071]
[0072] In summary, as demonstrated by Examples 1-4 and Comparative Example 1, under conditions of high-temperature treatment, atmospheric pressure treatment cannot induce the formation of pearlite-like structures. However, through the present invention, for example, the 10 GPa high-pressure treatment in Example 1 yields approximately 15.2% pearlite-like structures. This indicates that the present disclosure does not rely on conventional high-temperature aging to induce cellular reactions, but rather lowers the activation threshold of low-temperature cellular reactions through high pressure, enabling controlled pearlite transformation of TiAl alloys at temperatures as low as 800°C, 700°C, or even lower.
[0073] In summary, the inventors of this invention have demonstrated that high pressure is the core factor in breaking through the temperature threshold of atmospheric pressure processes and inducing low-temperature cellular transformation to produce pearlite-like structures. This provides a novel and feasible technical path for accurately obtaining high-performance TiAl alloys with target content microstructures, especially for the preparation of TiAl alloys with precisely controlled pearlite-like structure content.
Claims
1. A method for preparing TiAl alloys with precisely controlled pearlite-like microstructure content, characterized in that, The composition of the TiAl alloy, in atomic percentage terms, is Ti-(42-45)Al-(2-5)Mn-(0.1-0.5)Mo-0.4W-0.2(B,C). The volume fraction of pearlite-like microstructure in the TiAl alloy is controlled between 8% and 30%. Specifically, it includes the following steps: Step 1: Ingredients Weigh the raw materials according to the atomic percentage of each element in the alloy and mix them evenly; Step 2: Melting The uniformly mixed raw materials obtained in step one are prepared into a uniformly composed ingot by vacuum induction melting. Step 3: Two-step heat treatment The ingot with uniform composition obtained through step two is subjected to a two-step heat treatment to obtain the initial microstructure; Step 4: Machining The heat-treated ingot obtained through step three is machined into a cylinder with a certain length-to-diameter ratio for subsequent use. Step 5: High Temperature and High Pressure Experiment The machined cylindrical ingot is placed in a large-cavity high-temperature and high-pressure device and loaded for 2 to 5 hours under a pressure of 5 to 15 GPa and a temperature of 700 to 1000℃ to obtain a pearlescent structure with the target content.
2. The preparation method according to claim 1, characterized in that, The alloy composition, expressed as an atomic percentage, is Ti-44Al-3Mn-0.4Mo-0.4W-0.2(B,C).
3. The method according to claim 1, characterized in that, In step five, the pressure is 10 GPa.
4. The method according to claim 1, characterized in that, In step five, the temperature is 800℃. The loading time is 3 hours.
5. The method according to claim 1, characterized in that, In step five, the pressure is first increased to 10 GPa by gradually increasing the pressure, and then heated to 800°C at a heating rate of 100°C / min and held for 3 hours.
6. The method according to claim 1, characterized in that, In step five, after the target amount of pearlescent tissue is obtained by enduring the pressure and temperature conditions for the specified loading time in the large cavity high temperature and high pressure device, it is rapidly cooled to room temperature and finally restored to normal pressure through step-by-step depressurization.
7. The preparation method according to claim 1, characterized in that, In step three, the two-step heat treatment process includes first heating the ingot to 1200-1300°C, holding it at that temperature for 20-100 minutes, and then air-cooling it to room temperature; then heating the ingot to 850°C, holding it at that temperature for 2-5 hours, and then furnace-cooling it.
8. The preparation method according to claim 7, characterized in that, In step three, the two-step heat treatment process includes first heating the ingot to 1270°C and holding it for 30 minutes, then air cooling it to room temperature, and then heating the ingot to 850°C, holding it for 3 hours, and then furnace cooling it.
9. The preparation method according to claim 1, characterized in that, The content of the pearloid tissue is 10% to 30%.
10. The preparation method according to claim 8, characterized in that, The content of the pearloid tissue is 10% to 18%.